FA01.02: THE EFFECT OF POSTOPERATIVE COMPLICATIONS AFTER MIE ON LONG-TERM SURVIVAL: A RETROSPECTIVE, MULTI-CENTER COHORT STUDY. (14th September 2018) - Fransen, Laura; Berkelmans, Gijs; Asti, Emanuele; Van Berge Henegouwen, Mark; Berlth, Felix; Bonavina, Luigi; Brown, Andrew; Bruns, Christiane; Gisbertz, Suzanne; Grimminger, Peter; Gutschow, Christian; Hölscher, Arnulf; et al.
Abstract: Background: Esophagectomy has a high incidence of postoperative morbidity. Complications lead to a decreased short-term survival, however the influence of those complications on long-term survival is still unclear. Most of the performed studies are small, single center cohort series with inconclusive or conflicting results. Minimally invasive esophagectomy (MIE) has been shown to be associated with a reduced postoperative morbidity. In this study, the influence of complications on long-term survival for patients with esophageal cancer undergoing a MIE were investigated. Methods: Data was collected from the EsoBenchmark database, a collaboration of 13 high-volume centers routinely performing MIE. Patients were included in this database from June 1, 2011 until May 31, 2016. Complications were scored according to the Clavien-Dindo (CD) classification for surgical complications. Major complications were defined as a CD grade ≥ 3. The data were corrected for 90-day mortality to correct for the short-term effect of postoperative complications on mortality. Overall survival was analyzed using the Kaplan Meier, log rank- and (uni- and multivariable) Cox-regression analyses. Results: A total of 926 patients were eligible for analysis. Mean follow-up time was 30.8 months (SD 17.9). Complications occurred in 543 patients (59.2%) of which 39.3% had a major complication. Anastomotic leakage (AL) occurred in 135 patients (14.5%) of which 9.2% needed an intervention (CD grade ≥ 3). A significant worse long-term survival was observed in patients with any AL (HR 1.73, 95% CI 1.29–2.32, P < 0.001) and for patients with AL CD grade ≥3 (HR 1.86, 95% CI 1.32–2.63, P < 0.001). Major cardiac complications occurred in 18 patients (1.9%) and were related to a decreased long-term survival (HR 2.72, 95% CI 1.38–5.35, p 0.004). For all other complications, no significant influence on long-term survival was found. Conclusion: The occurrence and severity of anastomotic leakage and cardiac complications after MIE negatively affect long-term survival of esophageal cancer patients. Disclosure: All authors have declared no conflicts of interest.